Healthcare Access for People Experiencing Homelessness in Low-, Middle-, and High-Income Countries: A Comparative Policy Analysis - Gold, Samantha; Oudshoorn, Abe (International Journal on Homelessness, 2026)
Homelessness and inadequate housing affect approximately 1.6 billion people worldwide. Despite making up a fraction of the population, people experiencing homelessness (PEH) have higher rates of physical and mental health complications compared to the rest of the population with increased barriers to accessing necessary health care services. Therefore, this comparative policy analysis explores healthcare access for PEH and how this differs in low-, middle-, and high-income countries using the representative countries of Rwanda, Colombia, and Canada respectively. Comparisons and contrasts were made by analyzing the homelessness situation and the healthcare access barriers for PEH in each of these nations. Analysis was conducted using a combination of scientific and grey literature to understand each country’s experiences and the Voluntary National Review (VNR) reports to understand governmental perspectives. Through analysis, it became evident that the challenges PEH face regarding healthcare access are similar across countries. However, legal regulations and attitudes by the public and governmental bodies influence specific situational treatments and what is being done to combat these barriers, creating differences in PEH’s experiences.